Digital research and implementation of cloud-network planning of telecom operators - Xiaoming XIONG; Jing ZHAO (Dianxin kexue)
Based on the perspective of digital transformation of telecom operators, a data-driven cloud-network development planning system was proposed systematically, six key digital capabilities were built, and a cloud-network planning digital platform was designed and implemented, which could be used for scenarios such as fine planning of target networks, accurate prediction of edge computing, etc., and the application prospects of digital twins in the field of future cloud-network planning were discussed.The proposed system has guiding and reference significance for operators to promote cloud-network integration strategies and promote high-quality development.